Silica-Based Stationary Phase with Surface Bound N-Acetyl-glucosamine for Hydrophilic Interaction Liquid Chromatography - Vaithilingam Rajendiran; Ziad El Rassi (Molecules, 2023)
A hydrophilic silica-based stationary phase with surface bound N-acetylglucosamine (GlcNAc-silica) was prepared in house and characterized physically via Fourier transform infrared (FTIR) analysis and thermogravimetric analysis (TGA) and chromatographically over a wide range of mobile phase compositions. While both FTIR and TGA confirmed the attachment of the GlcNAc ligands to the silica surface, the chromatographic evaluation of GlcNAc-silica with polar and slightly polar standard solutes (e.g., sugars, nucleic acid fragments, phenolic, and benzoic acid derivatives) yielded the typical hydrophilic interaction liquid chromatography (HILIC) behaviors in the sense that retention increased with increases in solute polarity and the organic content (i.e., acetonitrile) of the hydro-organic mobile phase (i.e., ACN-rich mobile phase). Sugars derivatized with 1-naphthylamine (1-NA) and 2-aminoanthrcene (2-AA) such as xylose, glucose, and short chains maltooligosaccharides constituted the most polar species for HILIC retention evaluation, and in addition, the maltooligosaccharides offered a polar homologous series for gauging the hydrophilicity of GlcNAc-silica in analogy with alkylbenzene homologous series and other nonpolar homologues for evaluating the hydrophobicity of non-polar stationary phases. On the other hand, the benzoic acid and phenolic acid derivatives were the probe solutes for evaluating the HILIC retention dependence of ionizable solutes on the pH of the mobile phase. Similarly, the nucleobase and nucleoside weak basic solutes as well as some typical cyclic nucleotide acidic solutes allowed for the examination of the dependence of solute retention on the pH of the mobile as well as the polarity of the species.